Wave topology of stellar inertial oscillations - Armand Leclerc; Guillaume Laibe; Nicolas Perez (Physical Review Research)
Inertial waves in convective regions of stars exhibit topological properties linked to a Chern number of 1. The first of these is a unique, unidirectional, prograde oscillation mode within the cavity, which propagates at arbitrarily low frequencies for moderate azimuthal wave numbers. The second are phase singularities around which the phase winds in Fourier space, with winding numbers ν=±1 depending on the hemisphere. Phase winding is a collective effect over waves propagating in all directions that is strongly robust to noise. This suggests a topology-based method for wave detection in noisy observational data.